The Role Of Pregnancy Age, Blood Pressure And Vitamin D Deficit On Urine Protein Levels In Pregnant Women: A Study In Rural Population - Eka Dewi Retnosari; Marlinda Marlinda (International Journal Scientific and Professional (IJ-ChiProf), 2022)
Preeclampsia is a potentially dangerous pregnancy complication characterized by high blood pressure and protein levels in the urine that are prone to occur in the third trimester. Urine protein levels have been known as a definite indicator of preeclampsia cases and are also determinants of the severity of preeclampsia experienced by pregnant women. The incidence of preeclampsia accounts for 3-8% of all pregnancies and is the cause of the most maternal deaths in Indonesia. The purpose of this study was to determine the risk factors that contribute to the severity of preeclampsia through urine protein levels in pregnant women. The Method used an Analytical observation design with a crossectional approach to analyze data obtained from 76 pregnant women in Muara Enim Regency, Indonesia, who met the inclusion criteria in this study. The results show a significant association of risky gestational age, blood pressure, and deficiency vitamin D with urine protein levels in pregnant women. At the same time, the age and Body Mass Index (BMI) of pregnant women proved not to be significantly related to the urine proteins of pregnant women. The Conclusion is Prevention and treatment can be done by knowing the predictors that cause the occurrence of urine protein in pregnant women. Education about the detection of risk factors becomes essential to be conveyed by health workers to mothers undergoing pregnancy or entering the second trimester of pregnancy.